Training Residents in Hospital Medicine: The Hospitalist Elective National Survey. Issue 9 (26th March 2018) - Ludwin, Steven; Harrison, James D.; Ranji, Sumant; Sharpe, Bradley A.; Kneeland, Patrick
Abstract : As the feld of hospital medicine expands, internal medicine residency programs can play a role in preparing future hospitalists. To date, little is known of the prevalence and characteristics of hospitalist‐focused resident rotations. We surveyed the largest 100 Internal Medicine Residency Programs to better understand the prevalence, objectives, and structure of hospitalist‐focused rotations in the United States. Residency leaders from 82 programs responded (82%). The prevalence of hospitalist‐focused rotations was 50% (41/82) with an additional 9 programs (11%) planning to start one. Of these 41 rotations, 85% were elective rotations and 15% were mandatory rotations. Rotations involved clinical responsibilities, and most programs incorporated nonclinical curricular activities such as teaching, research, and work on quality improvement and patient safety. Respondents noted that their programs promoted autonomy, mentorship, and "real‐world" hospitalist experience. Hospitalist‐focused rotations may supplement traditional inpatient rotations and teach skills that facilitate the transition from residency to a career in hospital medicine.